Should childhood MMR vaccination be compulsory? Rights, duties and the public interest - Sheather, Julian (Landes Bioscience, 2013)
When children and young people lack the capacity to make decisions about their care and treatment, decisions have to be made on their behalf based on an assessment of their welfare or interests. In law, parents, or others with the relevant parental responsibility, are ordinarily regarded as the appropriate decision-makers. One way of framing this is to say that parents have certain decision-making rights with respect to their children. Such rights, however, are not generally regarded as absolute, rather they can be seen as secondary to and limited by the duties that parents have with regard to their children, duties to promote their welfare. It is against these parental duties that children could, at least in theory if not in practice, claim a right to certain kinds of protection. The legal rights of parents here, as opposed to the rights of the children, can be thought of as rights that secure for parents the freedom from interference necessary to fulfill the underlying duty.